PENGGUNAAN METODE GRAMATIKA-TERJEMAHAN DAN AUDIO-LINGUAL DALAM PEMBELAJARAN BAHASA ARAB - Asnah Asnah (IAIN Padangsidimpuan, 2014)
Studying Arabic language has aim for evolving reading ability in Arabic literature, and evolving skill in speaking Arabic. In developing reading ability and translate Arabic language is needed a good and appropriate methods in studying, one of them is grammatical-translate (Qawa’id wa-Tarjamah), it means that, ability of hanwu knowledge is trusted as absolute condition as a tool for understanding text or word in classic Arabic that is not have line, and another sigh. Moreover, Arabic language viewed as a tool of communication in modern life, so that, the point of studying Arabic is ability for using language with active, and capable for comprehending utterance or expression in Arabic language. For shaping this ability can use Audio-Lingua Method.